2022
DOI: 10.1002/ieam.4614
|View full text |Cite
|
Sign up to set email alerts
|

A geospatial and binomial logistic regression model to prioritize sampling for per‐ and polyfluorinated alkyl substances in public water systems

Abstract: As health-based drinking water standards for per-and polyfluorinated alkyl substances (PFAS) continue to evolve, public health and environmental protection decision-makers must assess exposure risks associated with all public drinking water systems in the United States (US). Unfortunately, current knowledge regarding the presence of PFAS in environmental systems is limited. In this study, a screening approach was established to: (1) identify and direct attention toward potential PFAS hot spots in drinking wate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 59 publications
0
12
0
Order By: Relevance
“…A case study was done using geospatial and statistical modelling for Kentucky, in which PFAS risk-areas were analysed, identifying potential nearby high-risk drinking water systems. The result of this research was verified by the sampling result generated by the Kentucky Department of Environmental Protection Agency (KDEP) [28]. KDEP sampled eighty-one (81) public drinking water systems, of which forty-three (43) are surface water sources and thirty-eight (38) are groundwater sources.…”
Section: Background and Summarymentioning
confidence: 59%
“…A case study was done using geospatial and statistical modelling for Kentucky, in which PFAS risk-areas were analysed, identifying potential nearby high-risk drinking water systems. The result of this research was verified by the sampling result generated by the Kentucky Department of Environmental Protection Agency (KDEP) [28]. KDEP sampled eighty-one (81) public drinking water systems, of which forty-three (43) are surface water sources and thirty-eight (38) are groundwater sources.…”
Section: Background and Summarymentioning
confidence: 59%
“…Although this approach mimics some natural exposure conditions, it might also neglect other important factors, such as the impact of the weathering process on the target compounds by the time an assessment is conducted (Suter, 1997). To further integrate a larger set of exposure parameters, geospatial or mapping tools have been incorporated in more recent risk assessments (Ojha et al, 2022). For example, in a study using available public data to conduct a geospatial analysis to visualize and prioritize sampling locations and potential PFAS hotspot locations, the authors were able to incorporate data from current and past users of the chemical, according to their industry, into their geospatial regression model with 76% accuracy in predicting the likelihood of PFAS prevalence in public drinking water systems while making recommendations for locations where PFAS would also present a risk to the public (Ojha et al, 2022).…”
Section: Figurementioning
confidence: 99%
“…To further integrate a larger set of exposure parameters, geospatial or mapping tools have been incorporated in more recent risk assessments (Ojha et al, 2022). For example, in a study using available public data to conduct a geospatial analysis to visualize and prioritize sampling locations and potential PFAS hotspot locations, the authors were able to incorporate data from current and past users of the chemical, according to their industry, into their geospatial regression model with 76% accuracy in predicting the likelihood of PFAS prevalence in public drinking water systems while making recommendations for locations where PFAS would also present a risk to the public (Ojha et al, 2022). To model exposure scenarios is crucial for chemicals widely used in a large number of industrial and nonindustrial sectors.…”
Section: Figurementioning
confidence: 99%
“…Per- and polyfluoroalkyl substances (PFAS) have been and continue to be used in industrial and commercial applications, and PFAS in waters may pose health risks to humans and ecosystems. Spatial proximity analysis studies show the occurrence of PFAS in ground or surface waters is related to the distance between the water body and PFAS manufacturing facilities, industries that use PFAS-based compounds, airports, and military sites, although other studies have shown multiple agricultural sources and pathways for PFAS occur with PFAS being found in rural streams with no obvious urban input. In some watersheds, specific industrial discharges to surface waters impact PFAS speciation and concentrations in drinking water intakes located downstream of the industrial discharger. , The U.S. Environmental Protection Agency (USEPA) Third Unregulated Contaminant Monitoring Rule or other drinking water monitoring efforts often used analytical methods with reporting limits of >1 ng/L, which may have missed the occurrence of PFAS at some drinking water locations. In many cases with detected PFAS, there were no apparent upstream PFAS-based industrial discharges, airports, military bases, or other known PFAS sources.…”
Section: Introductionmentioning
confidence: 99%
“…Per-and polyfluoroalkyl substances (PFAS) have been and continue to be used in industrial and commercial applications, and PFAS in waters may pose health risks to humans and ecosystems. 1−5 Spatial proximity analysis studies show the occurrence of PFAS in ground or surface waters is related to the distance between the water body and PFAS manufacturing facilities, industries that use PFAS-based compounds, airports, and military sites, 6 although other studies have shown multiple agricultural sources and pathways for PFAS occur with PFAS being found in rural streams with no obvious urban input. 7−10 In some watersheds, specific industrial discharges to surface waters impact PFAS speciation and concentrations in drinking water intakes located downstream of the industrial discharger.…”
Section: Introductionmentioning
confidence: 99%